COMPARISON OF TOTAL CHOLESTEROL LEVELS IN ACTIVE AND PASSIVE SMOKERS IN THE ALOEI SABOE REGIONAL GENERAL HOSPITAL AREA, GORONTALO CITY (Journal of Health, Technology and Science (JHTS), 2025)
Smoking and high cholesterol are risk factors for cardiovascular disease and events such as heart attacks and strokes. However, smoking habits in the community have not been eliminated. The purpose of this study was to compare total cholesterol levels in active smokers and passive smokers at Aloei Saboe Regional General Hospital in Gorontalo City.This research method uses a quantitative observational analytical approach. Type of observational analytical research. Research results: Results of research comparing total cholesterol levels in active smokers and passive smokers at Aloei Saboe Regional General Hospital from 30 samples.The results of this study indicate a significant difference in total cholesterol levels between active and passive smokers at Aloei Saboe Regional General Hospital. The data analysis shows a significance value < alpha (0.05) or (sig < 0.05), so Ha is accepted and H0 is rejected. The suggestion for future researchers is to conduct further research with a larger sample and to include additional research variables that affect the results, such as the physical activity and diet patterns of the research respondents.
Keywords: Total Cholesterol, Active Smokers, Passive Smokers